Synthesis and Photophysical Properties of Push–Pull Structures Incorporating Diazines as Attracting Part with a Fluorene Core. Issue 25 (19th July 2013) - Denneval, Charline; Moldovan, Oana; Baudequin, Christine; Achelle, Sylvain; Baldeck, Patrice; Plé, Nelly; Darabantu, Mircea; Ramondenc, Yvan
Abstract: We report, herein, the synthesis of new push–pull chromophores that incorporate a diazine ring as the electron‐withdrawing part and an N, N ‐dimethylaniline moiety as the electron‐donating part. Both of which are connected to a fluorene core. The length of the conjugated backbone was increased by incorporating ethynyl linkers and triazole rings on the both sides of the fluorene. The optical and two‐photon absorption (TPA) properties were investigated, which exhibitied high quantum yields (up to 70 %), significant Stokes shifts, and good TPA cross‐sections. Abstract : New push–pull fluorophores have been synthesized that contain a diazine ring as the electron‐withdrawing part and an N, N ‐dimethylaniline moiety as the electron‐donating part. Both of which are connected to a fluorene core. The syntheses of these structures consist of a copper‐catalyzed Huisgen 1, 3‐dipolar cycloaddition as well as Sonogashira and Suzuki cross‐coupling reactions.